A Study of Model‐Based Protective Fast‐Charging and Associated Degradation in Commercial Smartphone Cells: Insights on Cathode Degradation as a Result of Lithium Depositions on the Anode. Issue 12 (16th February 2021) - Besli, Münir M.; Subbaraman, Anantharaman; Pour Safaei, Farshad R.; Johnston, Christina; Schneider, Gerhard; Ravi, Nikhil; Christensen, Jake; Liu, Yijin; Doeff, Marca M.; Metzger, Michael; Kuppan, Saravanan
Abstract: The ever expanding mobile consumer electronic market has accelerated the need for safe and efficient fast‐charging approaches that improve the overall speed of battery charging without hastened deterioration of the battery performance. Herein, the impact of a resource inexpensive, physics‐based, electrochemically optimized fast‐charging algorithm (charging time < 2 h) for mobile devices is investigated. A critical difference in the amount and morphology of lithium deposits on the anode for cells fast‐charged without an optimized algorithm is observed and found to be the main cause of capacity decay. An in‐depth study of the LiCoO2 cathode regions opposite to pronounced lithium deposits on the anode reveals a "mirroring" phenomenon, i.e., a frozen monoclinic phase, and inactivity to relithiation. In operando hard X‐ray absorption spectroscopy reveals that degraded spots on harvested cathodes seem to be activated again and participate in the intercalation process when lithiated at low rates from lithium foil counter electrodes. On the other hand, tests at higher C‐rates, closer to the actual fast‐charging rate, reveal only negligible oxidation state changes and therefore poor performance. Abstract : Impact on degradation between a nonoptimized and an electrochemical model‐based fast‐charging algorithm. Heavy Li deposits on the anode leading to degradation in opposing cathode regions ("mirroring") are the consequence, if a non‐optimized, fast‐charging protocol is used for continuous charging, which can be avoided when using a model‐based fast‐charging protocol.